2009
DOI: 10.1074/jbc.m805782200
|View full text |Cite
|
Sign up to set email alerts
|

Deoxygenated Disaccharide Analogs as Specific Inhibitors of β1–4-Galactosyltransferase 1 and Selectin-mediated Tumor Metastasis

Abstract: The disaccharide peracetylated GlcNAc␤1-3Gal␤-O-naphthalenemethanol (disaccharide 1) diminishes the formation of the glycan sialyl Lewis X (Neu5Ac␣2-3Gal␤1-4(Fuc␣1-3)GlcNAc; sLe X ) in tumor cells. Previous studies showed that the mechanism of action of disaccharide 1 involves three steps: (i) deacetylation by carboxyesterases, (ii) action as a biosynthetic intermediate for downstream enzymes involved in sLe X assembly, and (iii) generation of several glycans related to sLe X . In this report, we show that Glc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…[17] Individual GalTs have been identified as molecular targets in a number of therapeutic areas, including cancer and infection. [18,19] For example, the inhibition of bacterial GalTs involved in the biosynthesis of lipopoly-and lipooligosaccharides of the Gram-negative cell envelope is a promising new stratGlycosyltransferases (GTs) are a large class of carbohydrateactive enzymes that are involved, in both pro-and eukaryotic organisms, in numerous important biological processes, from cellular adhesion to carcinogenesis. GTs have enormous potential as molecular targets for chemical biology and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Individual GalTs have been identified as molecular targets in a number of therapeutic areas, including cancer and infection. [18,19] For example, the inhibition of bacterial GalTs involved in the biosynthesis of lipopoly-and lipooligosaccharides of the Gram-negative cell envelope is a promising new stratGlycosyltransferases (GTs) are a large class of carbohydrateactive enzymes that are involved, in both pro-and eukaryotic organisms, in numerous important biological processes, from cellular adhesion to carcinogenesis. GTs have enormous potential as molecular targets for chemical biology and drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Gal residues are recognized by galectins that control cell-cell or cell-matrix interactions, apoptosis and signal transduction [3][4][5][6]. In cancer, these interactions can regulate the invasive and metastatic behaviour of cells [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that the GalT inhibition by 5-substituted UDP-Gal derivatives is broadly applicable to this enzyme class, and that despite of their polarity they are taken up by HL-60 cells 128 . Deoxygenated disaccharide analogs (per-O-acetylated GlcNAcβ1-3Galβ-O-naphthalenemethanol and C-3' and C-4' hydroxyl-modified analogs) competitively inhibited β4-GalT1, or related GalT enzymes in tumor cells in the tested concentration range: 0-50 µM 129 .…”
Section: Galactosylationmentioning
confidence: 99%